MicroRNA‐424 regulates epithelial‐mesenchymal transition of endometrial carcinoma by directly targeting insulin‐like growth factor 1 receptor. Issue 2 (6th September 2018) - Shu, Shanrong; Liu, Xiaoping; Xu, Ming; Gao, Xuesong; Fan, Jin; Liu, Huan; Li, Ruiman
Abstract: Although numerous miRNAs are reported to contribute to the carcinogenesis of malignant tumor, the specific role of miR‐424 in endometrial carcinoma is seldom reported. To explore the effect of miR‐424 on epithelial‐mesenchymal transition and its underlying mechanism, we detected miR‐424 expression in endometrial carcinoma tissue and cells. We found that miR‐424 was significantly downregulated in endometrial carcinoma tissues and cells, especially in HEC‐1B cells. To perform the functional analysis, we transfected HEC‐1B with miR‐424‐mi, miR‐424‐inh, mi‐control, and inh‐control, respectively. We found that overexpression of miR‐424 significantly decreases cell proliferation and migration, accompanied with the increased E‐cadherin/Vimentin expression and the transition of mesenchymal to epithelial cell phenotype. We identified that insulin‐like growth factor‐1 receptor (IGF‐1R) was a potential target of miR‐424 by computational analysis followed by luciferase reporter assays. Of note, we found that the downregulation of miR‐424 in HEC‐1B cells enhanced endogenous IGF‐1R expression. Further mechanistic analysis revealed that forced expression of IGF‐1R in miR‐424‐mim transfected cells remedied the weakened migration resulting from overexpression of IGF‐1R. Taken together, the results of the current study demonstrated that miR‐424 was a tumor suppressor for endometrial carcinoma and a favorable factor against tumor progression through targeting IGF‐1R, thus providing a target for the treatment of endometrial carcinoma. Abstract : 1. The effect of miR‐424 on epithelial‐mesenchymal (EMT) transition in endometrial carcinoma is explored. 2. The target gene of miR‐424 is investigated, which is IGF‐1R. 3. Through this research, we can find a new method to treat endometrial carcinoma.